Reinforcement of flaxseed mucilage-based edible film with nanocrystalline cellulose - Oeij, F. W.; Tee, Yee Bond; Nyam, K. L.; Chin, Nyuk Ling; A. Talib, Rosnita (Faculty of Food Science and Nutrition, Universiti Malaysia Sabah, 2017)
Flaxseed mucilage-based edible film plasticized with glycerol was previously prepared, with relatively low strength and stiffness which limits its application as food packaging material. With the aim to reinforce the mechanical properties, nanocrystalline cellulose (NCC) was added into the film in the present study. 1 wt.% to 5 wt.% of nanocrystalline cellulose suspension (NCC1 to NCC5) were prepared and added into the optimized formulation of flaxseed mucilage with 1 wt.% of glycerol (FMG). The nanocomposite films were formed via solution casting. They were studied in terms of mechanical, morphological, physical and antioxidant properties. As the NCC suspension increased, the tensile strength and Youn ’s modulus (or stiffness) significantly increased (to 2.3 MPa and 0.32 MPa) whereas the elongation at break decreased (to 40.3%) (p<0.05). From the morphology analyses of the FMG-N sam les’ tensile fracture surfaces, a lomeration of N within the matrix was o ser ed. This resulted in the lower mechanical reinforcement than anticipated. The addition of various loading of the NCC suspension did not significantly chan e the sam les’ colour which remained within the ellowish hue and trans arent ( > . ). While FMG itself had low antioxidant (at 9.13% of free radical scavenging activity and 13.8 mg gallic acid equivalent (GAE)), the addition of NCC did not significantly affect these antioxidant activities (p>0.05).